Digitalisasi Bimbingan Konseling pada Sekolah Menengah Atas - Muhammad Dzulfikar Fauzi; Maulana, Rizky Fenaldo; Wicaksono, Ardian Yusuf; Hajar, Granita; Al Faroby, Mohammad Hamim Zajuli (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
Guidance and Counseling (BK) has an important role in supporting the academic, social and emotional development of students in high school. However, recording and managing guidance and counseling services which are still done manually often creates obstacles, such as limitations in data retrieval, lack of privacy, and difficulties in maintaining student development on an ongoing basis. To overcome this problem, the use of digital systems in BK services is an effective solution. The BK digital system allows for more structured student data recording, faster access, as well as features such as counseling scheduling and student progress reports. This community service aims to build an application-based counseling guidance system that makes it easier to record counseling and violations committed by students. So far, counseling has been carried out by recording it in a counseling book, or if a customer commits it, it will be recorded on a violation card, which over time will fill the storage locker and it is also difficult to make mass data changes when a class changes guidance and counseling teachers. The counseling guidance application that has been created can meet the needs of guidance and counseling teachers for scheduling counseling and can see a brief description of the number of counseling activities in a particular month and can also print the results of the counseling